Differentiation of Fault and Load Change in HVDC System using Amplitude Tracking Square Wave - Ukil, Abishek (2015)
For a HVDC system, a reliable power system protection should be quick and precise in identifying fault. It is also equally important to ensure some events that could be mistaken for fault to not trigger false alarm, for example load change. Wavelet transform is one of the well-known tools that is able to achieve this purpose. In this paper, the fault analysis using a novel Amplitude Tracking Square Wave (ATSW) is studied. The algorithm is very easy to be implemented, as only timedomain analysis is involved. Notwithstanding the low complexity, it can work as effective as the wavelet transform, as proven by comparing the results obtained from these two signal processing techniques.